Nyai and Politics: The Role of Nyai Muhimmah in the Winning of the Candidate Pair Abdul Hafidz - Bayu Andrianto in the 2015 Rembang Regency Election - Ahmad Choirul Furqon; Nurul Nurhandjati (Jurnal Multidisiplin Madani, 2023)
This research discusses the role of the pesantren elite in winning the Abdul Hafidz - Bayu Andrianto candidate pair in the 2015 Rembang District Election. Islamic boarding schools specifically have not been carried out by many researchers. This is because most studies on Islamic boarding schools so far have focused on the kiai as the strongest figure who dominates various cultural, social, economic and political capitals of pesantren. The theory used to look at the practice of the 2015 Rembang local elections where Nyai Muhimmah was staged was James C. Scott's patron-client. He explained that the patron-client relationship can be seen through the pattern of relations that exist between the elite as patrons and the community as clients. By using a qualitative method, namely data collection through in-depth interviews and literature studies, the authors found that Nyai as a female pesantren leader was able to increase the electability of the couple Abdul Hafidz - Bayu Andrianto with absolute victory in all sub-districts even though she ran as a candidate from an independent path. Through her network, namely Islamic boarding schools, organizations and individuals, she succeeded in winning the pair Abdul Hafidz - Bayu Andrianto. Based on this, James Scott's theory has proven to be applicable and relevant to analyzing the patron-client relationship between Nyai and the people in Rembang Regency in the 2015 district election